Hvem ejer Kafka? - Butler, Judith (Passage - Tidsskrift for litteratur og kritik, 2011)
Judith Butler: “Who Owns Kafka?” The legal battle between the state of Israel and the German literary archive over the question of who owns Kafka’s work has prompted Israeli lawyers to argue that Kafka is an asset of the Jewish people and hence, of Israel. At stake is Kafka’s own complex cultural formation as a Prague Jew writing in German who alternately praised and disavowed Zionism. Equally troubling is the assumption that Israel represents the Jewish people and that Kafka might be conceived as an asset. Judith Butler proposes a reading of Kafka’s parables that quarrels with both sides of the legal case, seeking recourse to stories and fiction as a way of illuminating the limits of law and the diasporic (and messianic) alternative to Jewish nationalism.